2015
DOI: 10.1016/j.amepre.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Support for Physical Education as a Core Subject in Urban Elementary Schools

Abstract: Introduction Physical inactivity and childhood obesity are prevalent in American children, with increased vulnerability in minority, low-resource populations. The aim of this study was to quantify the impact of physical education (PE) on in-school physical activity quantity and intensity in urban minority children attending public elementary schools. Methods This observational study included elementary children (N=212; mean age, 9.9 years; 81.7% black) in Grades 2–5 attending urban public schools with high e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…Such long durations of MVPA were not even reached on days children engaged in both PE and OYS in our study. Two other studies (14,37) reported increases of MVPA by 50%–60% on days when school-age children attended PE classes, a result we could only confirm when comparing days without any sports activities to days with both PE and OYS. Regarding proportions of SB, we were able to confirm the results of Sigmund and colleagues (35) who observed a smaller proportion of total daily SB in children 9–11 yr old on days with PE compared with days without PE.…”
Section: Discussioncontrasting
confidence: 62%
“…Such long durations of MVPA were not even reached on days children engaged in both PE and OYS in our study. Two other studies (14,37) reported increases of MVPA by 50%–60% on days when school-age children attended PE classes, a result we could only confirm when comparing days without any sports activities to days with both PE and OYS. Regarding proportions of SB, we were able to confirm the results of Sigmund and colleagues (35) who observed a smaller proportion of total daily SB in children 9–11 yr old on days with PE compared with days without PE.…”
Section: Discussioncontrasting
confidence: 62%
“…Saint Louis Public Schools comply with the state-mandated requirement of 150 min of PA each week for elementary school students by providing 50 min/week of instructional PE by certified PE teachers and 20 min/day of recess ( Missouri Department of Elementary & Secondary Education , Minutes of Instruction). We previously reported that children in elementary grades achieve higher in-school daily steps and more minutes of MVPA on days with PE class compared to days without PE ( Castillo et al, 2015 ; Racette et al, 2015 ), supporting the National Academy of Medicine's recommendation that all elementary school students should have PE daily ( Institute of Medicine, 2013 ). The amount of PE class time that is spent engaged in MVPA has been observed to be <40% of the time allocated ( Nader, 2003 ; Racette et al, 2015 ), whereas the National Academy of Medicine recommendation is that ≥50% of PE class time should be spent engaged in vigorous or moderate-intensity PA ( Institute of Medicine, 2013 ).…”
Section: Discussionsupporting
confidence: 60%
“…For example, quality physical education predicts higher levels of physical activity in school. 6 School wellness policies that promote increased access to healthier foods and limit access to unhealthy foods have been linked to lower caloric intake 7 and improved student dietary quality 8,9 at school. There is emerging evidence that stronger state-level competitive food policies are associated with a healthier weight trajectory among middle school students.…”
Section: Introductionmentioning
confidence: 99%